Urgency of the Need for Learning to Read Local Wisdom-Based Hikayat Texts for Literature Learning in Grade 10 of High School - Eltias, Yumna; Faizah, Hasnah; Elmustian, Elmustian (JKTP: Jurnal Kajian Teknologi Pendidikan, 2024)
The purpose of this study was to see the urgency of learning to read local wisdom-based hikayat texts towards literature learning at Abdurrab Integrated Islamic Senior High School. This study is expected to provide new insights into literary studies, especially in learning classical Malay literature hikayat texts and achieving learning objectives. The method used in this study is quantitative with interview and questionnaire techniques. The data in this study were obtained through interviews conducted with teachers and the results of student needs questionnaires. The sample in this study was twenty tenth grade students. Based on the results of the interview, it can be seen that Indonesian language teachers who provide literature material require hikayat text learning with the implementation of hikayat text learning based on local wisdom. Based on the results of the student questionnaire, out of twenty students, seven students did not understand the hikayat text material and thirteen students understood the hikayat text enough without any integration of local wisdom in the learning process. Therefore, the urgency of learning to read local wisdom-based hikayat texts is very much needed in tenth grade Indonesian language learning to support the success of learning competencies and curriculum. Abstrak Tujuan penelitian ini untuk melihat melihat urgensi pembelajaran membaca teks hikayat berbasis kearifan lokal terhadap pembelajaran sastra di kelas X SMAIT Abdurrab. Manfaat penelitian ini diharapkan dapat memberikan wawasan baru dalam studi sastra dan mencapai tujuan pembelajaran yang sesuai dengan kondisi dan kebutuhan peserta didik. Penelitian menggunakan metode kuantitatif dengan teknik wawancara dan angket. Sampel penelitian ini didapatkan dari wawancara bersama guru dan mengambil data dari angket. Sampel dalam penelitian ini yaitu siswa kelas X SMA sebanyak 20 Siswa. Berdasarkan hasil dari wawancara guru dari 10 butir pertanyaan, guru membutuhkan pembelajaran teks hikayat untuk implementasi pembelajaran hikayat yang berbasis kearifan lokal dan berdasarkan hasil dari angket siswa didapatkan 7 orang siswa kurang dan 13 orang siswa cukup mengerti pembelaran teks hikayat tanpa adanya integrasi kearifan lokal di dalam proses pembelajaran.